2021
DOI: 10.1093/g3journal/jkab320
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early genomic prediction for recurrent selection in an upland rice synthetic population

Abstract: Population breeding through recurrent selection is based on the repetition of evaluation and recombination among best-selected individuals. In this type of breeding strategy, early evaluation of selection candidates combined with genomic prediction could substantially shorten the breeding cycle length, thus increasing the rate of genetic gain. The objective of the present study was to optimize early genomic prediction in an upland rice (Oryza sativa L.) synthetic population improved through recurrent selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 74 publications
4
13
1
Order By: Relevance
“…If successful, this would allow for a very efficient search of potential new donors for high grain Zn concentrations. The prediction accuracy of 0.51 achieved in this study is similar to the PA ranging from 0.33 to 0.69 in wheat (Velu et al 2016 ), of 0.43–0.73 reported for maize (Mageto et al 2020 ) and of 0.51 in upland rice (Baertschi et al 2021 ). The present study was conducted in two low-input farmers’ fields rather than under the more controlled conditions one may encounter on research farms and that the PA achieved here is comparable to PAs reported from research farms is further suggestive of GP being a suitable approach for identifying potential donors from gene banks.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…If successful, this would allow for a very efficient search of potential new donors for high grain Zn concentrations. The prediction accuracy of 0.51 achieved in this study is similar to the PA ranging from 0.33 to 0.69 in wheat (Velu et al 2016 ), of 0.43–0.73 reported for maize (Mageto et al 2020 ) and of 0.51 in upland rice (Baertschi et al 2021 ). The present study was conducted in two low-input farmers’ fields rather than under the more controlled conditions one may encounter on research farms and that the PA achieved here is comparable to PAs reported from research farms is further suggestive of GP being a suitable approach for identifying potential donors from gene banks.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the heritability for grain Zn concentrations (H 2 = 0.79) was larger than for GY (H 2 = 0.40). High heritability (> 0.70) for grain Zn has also been reported elsewhere (Swamy et al 2016 , 2018 ; Baertschi et al 2021 ).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations